(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This work is focused on nucleation stages during isothermal austenite transformation in two types of Vanadium micro-alloyed steels. Isothermal treatment was carried out in the temperature range 350 to 600 C. Metallographic evaluation using optical and scanning electron microscopy (SEM) enabled determination of the nucleation curves of isothermally decomposed austenite. Three curves are found to be relevant to this initiation stage of transformation: first curve is related to grain boundary nucleated ferrite (GBF), second curve is related to intragranularly nucleated ferrite (IGF) and the third to pearlite (P) curve. GBF and IGF curves are divided into two regions, which represents the high temperature and the low temperature segments as consequence of either displacive nature of transformation or diffusion transformation. Addition of Ti to V – micro-alloyed steel in this work seems to be balanced by a slightly higher C and Mn content, leading to limited effect on nucleation stage of austenite decomposition.